2004
DOI: 10.1111/j.1468-2982.2004.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Migraine: A Cross-Sectional Study in Patients Aged Three to Sixty-Nine

Abstract: We investigated 260 consecutive patients classified as migraine cases aged 3-69 at two tertiary headache centres, one for children and adolescents and the other for adults to evaluate the relationship between age and clinical features of migraine cross-sectionally. We only included subjects with definite migraine without or with aura and we excluded subjects with coexisting tension-type headache, medication overuse and/or other clinically relevant disorders. The percentage of males decreased markedly from chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 23 publications
9
57
1
2
Order By: Relevance
“…Interestingly, the clinical characteristics of migraine change with age [16] and as comorbidities increase [11]. In a study of 260 consecutive patients with migraine, ranging in age from 3 to 69 years, marked differences in clinical features were observed with age [17]. The percentage of males with migraine decreased markedly from childhood to adulthood.…”
mentioning
confidence: 99%
“…Interestingly, the clinical characteristics of migraine change with age [16] and as comorbidities increase [11]. In a study of 260 consecutive patients with migraine, ranging in age from 3 to 69 years, marked differences in clinical features were observed with age [17]. The percentage of males with migraine decreased markedly from childhood to adulthood.…”
mentioning
confidence: 99%
“…The same group reported changes in symptoms nearly identical with our experiences in the much wider age range of 3e69-year-old female migraineurs. 42 All these results reveal a fairly congruent tendency of the changes in the prevalence of migraine features in children (Table 5). …”
Section: Phonophobia (G) Photophobia (G) Unilateral (G) Pulsating (B)mentioning
confidence: 58%
“…Distinct pain location in migraine headaches is (p<0.0001) connected with the age of the children and their ability to interpret it [14]. Wöber-Bingöl et al [15] found in 260 consecutive patients aged 3-69 that headache duration and the prevalence of unilateral, pulsating pain, photophobia and phonophobia increased in females, whereas the prevalence of aggravation by physical activity decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Wöber-Bingöl [15] found that intensity of pain, aggravation of headache by physical activity, nausea and vomiting were the most important features, and the quality of pain, photo-and phonophobia were less helpful in the differential diagnosis of migraine and tension-type headache.…”
Section: Discussionmentioning
confidence: 99%